Antimicrobial, antifungal and antioxidant activities of bee glue ethanol and aqueous extracts - Nabi Shariatifar; Akram Janghorban; Rezvan Rahimnia; Amir Sasan Mozaffari Nejad (Journal of Biological Research, 2018)
Food-borne pathogens is a group of micro-organisms that cause food-borne illness, thus the research for finding effective drugs against this infection is necessary. The purpose of this study determines antibacterial, antioxidant activity antifungal of bee glue ethanol and aqueous extracts. Antibacterial and antifungal activities of extracts were evaluated against food-born (Escherichia coli, Staphylococcus aureus, Bacillus cereus, Vibrio cholerae and Candida albicans) purchased from Boali hospital on by the well diffusion method. Broth serial dilution method was doing to find the Minimal Inhibitory Concentration (MIC) and the agar dilution method to find the Minimal Bacterial Concentration (MBC) of extracts. The antioxidant activity of the extracts assaying by 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. Ethanol extract of bee glue was found the most effective against S. aureus strains (inhibition zone=27±0.87 mm) than E. coli strains (inhibition zone=5.5±0.37mm). Aqueous extract of propolis was found the most effective against S. aureus strains (inhibition zone=14.5±0.75 mm) than E. coli strains (inhibition zone=3.5±0.5mm) and C. albicans (inhibition zone=10±0.5 mm). The MIC and MBC values of the extracts ethanol and aqueous most effective against B. cereus strains were 0.3125, 0.625, 0.3125 and 1.25 mg/mL than E. coli strains 0.625, 1. 25, 2.5 and 50 mg/mL. and also for C. albicans was 0.625, 1.25, 1.25 and 2.5 mg/mL. IC50 ethanol and aqueous extracts of propolis were 8±0.25 and 45±1.75, respectively. This study was to assess the Antibacterial, antifungal and antioxidant activities activities of bee glue extracts in in vitro.